2018
DOI: 10.1371/journal.pone.0192022
|View full text |Cite
|
Sign up to set email alerts
|

Self-compassion moderates the perfectionism and depression link in both adolescence and adulthood

Abstract: BackgroundPsychological practitioners often seek to directly change the form or frequency of clients’ maladaptive perfectionist thoughts, because such thoughts predict future depression. Indirect strategies, such as self-compassion interventions, that seek to change clients’ relationships to difficult thoughts, rather than trying to change the thoughts directly could be just as effective. This study aimed to investigate whether self-compassion moderated, or weakened, the relationship between high perfectionism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
79
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 63 publications
13
79
0
1
Order By: Relevance
“…Empirical data from non-clinical populations is supportive of this idea. Self-compassion partially mediated the association between perfectionism and depression in university students (Mehr and Adams, 2016); while in another study (Ferrari et al, 2018), moderation analyses revealed that self-compassion was associated with diminished strength of the relationship between maladaptive perfectionism and depression in two independent samples (adolescents and adults). In a related study, we found that self-compassion mediated the relationship between vulnerability to BD and psychological distress in a non-clinical sample (Yang et al, 2018).…”
Section: Perfectionism In Bipolar Disordermentioning
confidence: 87%
“…Empirical data from non-clinical populations is supportive of this idea. Self-compassion partially mediated the association between perfectionism and depression in university students (Mehr and Adams, 2016); while in another study (Ferrari et al, 2018), moderation analyses revealed that self-compassion was associated with diminished strength of the relationship between maladaptive perfectionism and depression in two independent samples (adolescents and adults). In a related study, we found that self-compassion mediated the relationship between vulnerability to BD and psychological distress in a non-clinical sample (Yang et al, 2018).…”
Section: Perfectionism In Bipolar Disordermentioning
confidence: 87%
“…In a meta‐analysis and recent studies, higher levels of self‐compassion were associated with lower levels of depression, anxiety, and stress. Self‐compassion significantly moderated the relationship between self‐coldness (ie, self‐judgment, isolation, and overidentification), maladaptive perfectionism, and depressive symptoms . Fear of receiving compassion from others was positively associated with depression, anxiety, and stress .…”
Section: Introductionmentioning
confidence: 96%
“…Self-compassion significantly moderated the relationship between self-coldness (ie, self-judgment, isolation, and overidentification), maladaptive perfectionism, and depressive symptoms. 26,27 Fear of receiving compassion from others was positively associated with depression, anxiety, and stress. 28 Fear of compassion from others also played the moderator role in enhancing the relationship between self-criticism and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, self-criticism⎯the inverse of self-compassion⎯has been found to mediate the relationship between unhealthy perfectionism and distress (James, Verplanken, & Rimes, 2015), implicating self-criticism as a potential process that maintains poor outcomes in perfectionism. Furthermore, self-compassion has been found to weaken the relationship between maladaptive perfectionism and depression (Ferrari, Yap, Scott, Einstein, & Ciarrochi, 2018), which could indicate its utility as a treatment target in clinical perfectionism.…”
mentioning
confidence: 99%